(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2017)
A mathematical model for signals description of the autodyne short-range radar (ASRR) with the simultaneous pulse amplitude modulation (PAM) and the linear frequency modulation (FM) is considered. The peculiarities of signal formation are described, which are obtained from the radar distributed object in the form of an ensemble of an arbitrary number of point-type reflectors. Signal calculations are carried out by the offered approach of the step method for the case of two point reflectors on the radar object located at various distances from ASRR. The distinctive signal properties formed at reception of the first and further emissions reflected form the radar object are established. After sending of the probe emission, the reception of the first reflected emission from the set of shining points is accompanied by linear signal superposition formation from separate reflectors. The reception of further reflections causes an appearance of combinational signal interaction from separate reflectors. The character and degree of such an interaction is defined by the feedback parameter of ASRR, which depends on the autodyne frequency deviation and delay time of reflected emission. Results of ASRR experimental investigations with simultaneous PAM and the linear FM are obtained using the oscillating module made on the Gunn diode of 8mm-range.